Analisis Kinerja Relai Arus Lebih pada PLTU Embalut PT. Cahaya Fajar Kaltim Unit 1×60 MW dengan Simulasi - Agung Prasetyo; Rusda Rusda; Masing Masing (Politeknik Negeri Ujung Pandang, 2019)
Embalut power plant is one of the power plants that supply electricity in East Kalimantan. The plant which is operated by PT. Cahaya Fajar Kaltim, has one PLTU unit with a capacity of 2x25 MW and another with the capacity of 1x60 MW. As an electricity company that must keep continuity of electric supply to customers, a reliable electrical system is necessary. Such reliable system requires protection system to detect a problem and avoid electrical equipment damage. A proper protection system should isolate the affected area and prevent black out on the other area. A type of problem may occur is a short circuit. This study analyzes the performance of overcurrent relays in 1 × 60 MW power plant unit. The analysis was performed through ETAP 12.6.0 software which was also used to design the single line diagrams, calculate the setting currents of short circuit current, also to simulate the coordination of several overcurrent relays in the system. Adjustment of the current and time value in the overcurrent relay is obtained from the result of manual calculations. The results then are displayed in the form of a characteristic curve. Afterwards, a simulation is performed in a situation where three-phase short circuit occurs at BFWP 1.3 Bus, TR AUX.3 Bus and TR 3A.3 Bus. The results show that the overcurrent relays work properly and could overcome the problem quickly.